Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2008
DOI: 10.1002/elan.200804338
|View full text |Cite
|
Sign up to set email alerts
|

Nanofibrillar Cellulose‐Chitosan Composite Film Electrodes: Competitive Binding of Triclosan, Fe(CN)63−/4−, and SDS Surfactant

Abstract: Glassy carbon electrodes are modified with a thin film of a cellulose-chitosan nanocomposite. Cellulose nanofibrils (of ca. 4 nm diameter and 250 nm length) are employed as an inert backbone and chitosan (poly-d-glucosamine, low molecular weight, 75 -85% deacetylated) is introduced as a structural binder and "receptor" or molecular binding site. The composite films are formed in a solvent evaporation method and prepared in approximately 0.8 mm thickness. The adsorption of three molecular systems into the cellu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0

Year Published

2010
2010
2022
2022

Publication Types

Select...
4
4

Relationship

1
7

Authors

Journals

citations
Cited by 17 publications
(9 citation statements)
references
References 38 publications
0
9
0
Order By: Relevance
“…Owing to the relatively high affinity of sodium dodecylsulfate (SDS) to the CNFs/chitosan composite, the authors suggested that the CNFs/chitosan modified electrode could be potentially used for the accumulation and electrochemical detection of SDS and other anionic surfactants. 123 Hydrogen peroxide and glucose have also been detected using hybrid materials such as AuNPs/NCs. 96,124,125 The fabrication of AuNP/BC nanocomposites through a onestep biotemplated method by using poly(ethyleneimine) (PEI) as a linking and reducing agent for the synthesis of AuNPs within the scaffold of BC was first described by Zhang et al The fabricated AuNP/BC nanocomposites were found to be excellent supports for enzyme immobilization.…”
Section: Ncs In Optical (Bio)sensingmentioning
confidence: 99%
“…Owing to the relatively high affinity of sodium dodecylsulfate (SDS) to the CNFs/chitosan composite, the authors suggested that the CNFs/chitosan modified electrode could be potentially used for the accumulation and electrochemical detection of SDS and other anionic surfactants. 123 Hydrogen peroxide and glucose have also been detected using hybrid materials such as AuNPs/NCs. 96,124,125 The fabrication of AuNP/BC nanocomposites through a onestep biotemplated method by using poly(ethyleneimine) (PEI) as a linking and reducing agent for the synthesis of AuNPs within the scaffold of BC was first described by Zhang et al The fabricated AuNP/BC nanocomposites were found to be excellent supports for enzyme immobilization.…”
Section: Ncs In Optical (Bio)sensingmentioning
confidence: 99%
“…The relatively high affinity of sodium dodecyl sulfate (SDS) to the NFC/ chitosan composite was commended and has suggested that the NFC/chitosan-modified electrode could be potentially used for the accumulation and electrochemical detection of SDS and other anionic surfactants. 78 Hydrogen peroxide and glucose could also be detected using hybrid materials such as AuNPs/CNCs. Zhang et al studied the fabrication of AuNP/BC nanocomposites: they described the synthesis of AuNPs within the support of BC by a one-step biotemplated method using poly (ethylenimine) (PEI) as a linking and reducing agent.…”
Section: Cncs In Electrical Biosensingmentioning
confidence: 99%
“…The relatively high affinity of sodium dodecyl sulfate (SDS) to the NFC/chitosan composite was commended and has suggested that the NFC/chitosan-modified electrode could be potentially used for the accumulation and electrochemical detection of SDS and other anionic surfactants. 78 …”
Section: Nanocellulose In Biosensing and Bioimagingmentioning
confidence: 99%
“…Cellulose nanofibrils are obtained in colloidal form with negative surface charge (surface) and they can be bound onto electrode surfaces with a cationic polyelectrolyte such as chitosan [24] or poly(diallyldimethylamminum chloride) (PDDAC) [25]. Here, a layer-by-layer electrostatic deposition approach is chosen to deposit very thin films of cellulose nanofibrils bound with PDDAC onto ITO electrode substrates (see Experimental).…”
Section: Formation and Characterisation Of Carbonisedmentioning
confidence: 99%